Rain, Snow and Frozen Soil: Open Questions from a Porescale Perspective with Implications for Geohazards - Ivo Baselt; Thomas Heinze (Geosciences, 2021)
Climate change is already affecting high mountain regions, such as the European Alps. Those regions will be confronted with a significant rise of temperatures above the global average, and more and heavier rain events, also during wintertime. The system response to the coincidence of rain, snow, and possibly frozen soil depends on the almost infinite number of possible combinations of thermo-hydraulic states of the involved phases. Landslides, snow avalanches, debris flows, or extensive surface runoff are just a few of the possible hazardous outcomes. With rising temperatures and increased precipitation, those hazardous outcomes are expected to occur even more frequently in the future, requiring a better understanding of those coupled processes for hazard mitigation strategies. The macroscopic phenomena are controlled by porescale processes, such as water freezing and ice grains blocking pores, which are only barely understood. The strong coupling between thermal state and hydraulic parameters, the possible phase change, and material heterogeneity pose great challenges for investigation. This work provides an overview of documented hazard events regarding rain, snow, and possibly frozen soil. The current state in theoretical and experimental research is presented before several knowledge gaps are derived and possible techniques to address those gaps are discussed.